Value of computed tomography in patients with stroke: Oxfordshire Community Stroke Project. Issue 6463 (19th January 1985) - Sandercock, P; Molyneux, A; Warlow, C
Abstract : The usefulness of computed tomography (CT) was assessed in 325 consecutive patients with a "clinically definite first stroke" from a community stroke register. CT detected five "non-stroke" lesions (two cerebral gliomas, one cerebral metastasis, and two subdural haematomas), a frequency of 1.5%. Five patients were identified with cerebellar haemorrhage, but only one survived long enough to have a CT scan. CT was useful in excluding intracranial haemorrhage as the cause of the stroke in four patients receiving anticoagulants and seven receiving antiplatelet treatment; it showed intracranial haemorrhage in one patient taking aspirin. Forty six patients were in atrial fibrillation at the time of their stroke; four had intracranial haemorrhages and three had haemorrhagic cerebral infarcts. Nineteen patients with presumed ischaemic minor stroke were considered suitable for carotid endarterectomy; CT showed small haemorrhages in two. The CT scan provides very useful information in a minority (up to 28%) of patients with first stroke, who can be selected on quite simple criteria: (a) doubt (usually because of an inadequate history) whether the patient has stroke or a treatable intracranial lesion; (b) the possibility of cerebellar haemorrhage or infarction; (c) the exclusion of intracranial haemorrhage in patients who either are already taking or likely to need antihaemostatic drugs or are being considered for carotid endarterectomy; (d) if the patient deteriorates in a fashion atypical of stroke.